Acute Myeloid Leukemia Characterized by Four CEBPA Mutations. (21st September 2018) - Beckman, Amy; Meredith, Matthew; Rangan, Aruna; Thyagarajan, Bharat; Yohe, Sophia; Mroz, Pawel
Abstract: The CCAAT enhancer binding protein alpha (CEBPA) is a tumor suppressor gene located within 19q13.1 that encodes transcription factor involved in granulocytic differentiation. CEBPA mutation is considered a primary event in leukemogenesis and shows three patterns: (1) single allele mutated, ~50% of CEPBA mutated AML; (2) double mutations typically involving an N-terminal and a C-terminal and assumed to be biallelic; and (3) a homozygous mutation due to loss of heterozygosity. The new WHO 2017 classification includes an AML with a biallelic CEBPA mutations category associated with favorable prognosis. Here, we present a case of a 65-year-old male with AML with 21% blasts, dysgranulopoiesis, and dysmegakaryopoiesis. Cytogenetics revealed 46, XY[20] karyotype and Sanger sequencing showed three CEBPA variants: (1) c.68dup; p.His24Alafs*84, a pathogenic frameshift mutation located within the N-terminal region; (2) c.496G>T; p.Glu166* pathogenic, nonsense mutation located in transactivation domain 2 (TAD2) near the N-terminus; and (3) c.879_880insTTATCT, p.Asn293_Ile294insLeuSer, an in-frame variant of undetermined significance. The NGS showed the variant allele frequency (VAF) of 7.9%, 15.4%, and 17.3%, respectively, as well as a fourth CEBPA mutation, c.992T>A p.Leu331Gln with VAF of 4%. Additionally, NRAS c.38G>A, p.Gly13Asp mutation was detected. After 7 + 3 induction chemotherapy, bone marrow showed persistent AML with ~39% blasts and Sanger sequencing showed one CEBPA mutation, c.879_880insTTATCT. The initial VAFs suggested the presence of possibly two biallelic leukemic clones, each characterized by two CEBPA mutations; however, the follow-up BM sample showed only one CEBPA variant that was originally classified as VUS. We plan to perform the NGS study on the follow-up sample as well as attempt a long-read SMRT sequencing to elucidate whether the original mutations were in fact biallelic. To our knowledge, this represents the first reported case of a patient with AML and four CEBPA mutations.